O Liberalismo - Hobhouse, Leonard; Sternick, Ivan; Leite, Mateus; Fernandes, Rauan; de Sousa, Maxswell; Guedes, Gabriel (Princípios: Revista de Filosofia (UFRN), 2022)
Tradução da obra "Liberalism" (1911), de Leonard Trelawny Hobhouse.